Application of Graphene Materials in Energy Storage and Conversion - Zhang, Yunlu (Transactions on Environment, Energy and Earth Sciences, 2026)
Graphene, a two-dimensional carbon nanomaterial, has emerged as a transformative component in energy storage and conversion due to its exceptional electrical conductivity (up to 10^8 S/m), high specific surface area (2.63 × 10^3 m²/g), and mechanical strength (Young's modulus ~1.0 TPa). This review examines the pivotal role of graphene-based materials in advancing lithium-ion batteries, supercapacitors, fuel cells, and solar cells. In batteries, graphene composites enhance energy density and cycling stability, addressing issues like volume expansion in silicon anodes. For supercapacitors, graphene enables high capacitance and rapid charge-discharge cycles. In fuel cells, it improves electrocatalytic efficiency and membrane durability, while in solar cells, it serves as a transparent electrode to boost charge transport. Synthesis methods, including chemical vapor deposition and Hummers’ method, are discussed alongside challenges such as scalability, defect control, and cost-effective production. The future outlook is hybrid materials and AI-assisted optimization to provide sustainable energy solutions, which places graphene as one of the foundations of the future generation of energy technologies.
Keywords: Graphene, Energy Storage, Energy Conversion, Lithium-Ion Batteries, Supercapacitor.